Sistem Informasi Inventarisasi Barang Pada Poltekkes Kemenkes Jambi - Natio Adha, Prama; Devitra , Joni (LPPM Universitas Dinamika Bangsa, 2024)
Microsoft Excel and Microsoft Word are still used for managing the inventory of goods at the Health Polytechnic of the Ministry of Health in Jambi, but there are still a lot of issues with that management, such as mistakes being made when recording the inventory data of goods and available goods data frequently being incorrect with the stock in the warehouse as well as data files. The search for inventory data is time-consuming because the inventory of items is still kept on the laptop and backed up to a flash drive. The Ministry of Health, Jambi, too lacks an inventory webpage at Poltekkes. The goal of this study is to develop an online system for tracking commodities inventories. Object-based modeling is used to explain the analysis and design of a web-based products inventory information system at the Health Polytechnic of the Ministry of Health of Jambi, namely in the form of use case diagrams, activity diagrams, and class diagrams. A prototype design is the study's output. Suggestions for the Health Polytechnic of the Ministry of Health, Jambi: In order to be used to help the process of inventorying goods at the Health Polytechnic of the Ministry of Health Jambi, the design of a web-based goods inventory information system needs to be implemented and realized in the form of an application.